THE ROLE OF DUPLEX SCANNING OF VESSELS OF THE BASIN OF THE INTERNAL ILIAC ARTERY IN THE DIAGNOSIS OF UTERINE FIBROIDS - Karimov, A.Kh.; Yuldasheva, D.Yu.; Yulbarisov, A.A.; Irnazarova, D.Kh. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
Objective: To assess the role of duplex scanning of the pool of the internal iliac artery and the features of its angioarchitectonics in patients with uterine myoma. Material and methods: A prospective, non-randomized case-control study was conducted at the Women’s Health Center of the 2nd TMA clinic, including 152 women: a control group - 50 healthy women, a main group - 102 women with uterine myoma. The latter, in turn, were divided into subgroups - 53 women with symptomatic, 49 – with asymptomatic uterine myoma. Results: Duplex scanning of vessels of the basin of the internal iliac artery in women with uterine myoma is one of the main non-invasive and informative diagnostic methods for the diagnosis of hemodynamic changes in this disease. Depending on the type of blood supply to the node, it is possible to assess the growth of uterine fibroids, which provides a differentiated approach to therapeutic tactics. Conclusions: A study of the nature of the vascularization of uterine fibroids by duplex scanning opens up great prospects for non-invasive differential diagnosis to identify clinical and pathogenetic options for rapid growth and determine further tactics of patient management.